Comparison of Cross-Cultural Social Skills between Adolescents in International Schools, National Plus Schools, and Public Schools - Taufik Agung Pranowo; Rizky Andana Pohan; Panggih Wahyu Nugroho; Noorazman Bin Abd Samad (Jurnal Pendidikan Indonesia, 2026)
This research is motivated by the limited empirical studies on cross-cultural social skills (CCSS) among Indonesian adolescents, especially in comparisons across school types. However, differences in educational environment characteristics are thought to influence the development of students' cross-cultural competence. This study aims to analyze the CCSS levels of students in international schools, national plus schools, and public schools. The study used a quantitative, comparative-correlational design. The study subjects were 550 high school students selected through a proportionate stratified cluster sampling technique. Data were collected using the CCSS instrument, which has been tested for its validity and reliability. Data analysis was performed using a One-Way ANOVA and the Tukey HSD post-hoc test. The results showed significant differences among school types (p < 0.05), with international school students scoring highest on all five CCSS dimensions, followed by national plus schools, and public schools scoring lowest. These findings imply the importance of integrating multicultural perspectives and social-emotional learning in the public school curriculum. Thus, a multicultural educational environment plays a crucial role in developing youth's cross-cultural competence.